United States : 2001 Article IV Consultation-Staff Report; Staff Statement; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2001)
Sound fiscal and monetary policies have provided a strong foundation for the longest U.S. economic expansion on record. Executive Directors agreed that the U.S. economy strength had been supported by rising real income, enhanced profitability, and rising household wealth. Directors cautioned the need to reduce the domestic demand growth, and maintain monetary and fiscal policies. Directors expressed concern about the decline in personal saving, rise in household and corporate debt levels, and supported preemptive efforts to limit potential bank balance sheet risks.